PENGARUH PEMBERIAN EKSTRAK ETANOL BUNGA TELANG (Clitoria ternatea l.) TERHADAP KADAR INTERLEUKIN-1 β: Studi Eksperimental Terhadap Tikus Putih Jantan Galur Wistar Yang Diberi Paparan Asap Rokok - Nanisa Dewicinta Hadua; Eni Widayati (Jurnal Riset Multidisiplin Edukasi, 2026)
Cigarette smoke contains toxic substances such as carbon monoxide and nicotine that can trigger oxidative stress, which activates an inflammatory response, one of which is characterized by an increase in IL-1β levels. Ethanol extract of butterfly pea flower (Clitoria ternatea L.) contains flavonoids and anthocyanins as anti-inflammatory and antioxidant agents, which can suppress IL-1β levels. This study aims to determine the effect of butterfly pea flower ethanol extract on IL-1β levels in male Wistar rats exposed to cigarette smoke. This study is an experimental study with a post-test only control group design. The sample consisted of 30 male Wistar rats divided into 5 groups randomly, namely normal control (K0), negative control (exposed to cigarette smoke), treatment 1 (aspirin 9 mg/200gBW), treatment 2 (200 mg/kgBW blue pea flower extract), and treatment 3 (400 mg/kgBW ethanol extract of blue pea flower). The treatment lasted for 14 days, and on the 15th day, blood samples were collected using the ELISA method. Data analysis was performed using ANOVA followed by the Games-Howell post hoc test. The mean IL-1β levels were K(0) 47.43 ± 0.84 ng/ml, K(-) 179.67 ± 1.44 ng/ml, P1 69.64 ± 1.87 ng/ml, P2 79.63 ± 1.92 ng/ml, P3 64.09 ± 4.41 ng/ml. The analysis showed a significant difference between groups (p<0.05), with the greatest decrease in IL-1β levels in the 400 mg/kgBW ethanol extract of butterfly pea flower group. It can be concluded that ethanol extract of butterfly pea flower reduces IL-1β levels in mice exposed to cigarette smoke.